‘Chess studies’ for String Quartet: Composition based on chess - Alberto Hortigüela; Sara Carvalho (Revista Vortex)
This article proposes a first approach to the possibilities of adapting mathematical elements derived from chess to musical composition based on the analysis of the composition process of the work Chess Studies for String Quartet, composed in 2020 by the 1st author of this paper. The structure of its four movements arises from the superimposition of the geometry derived from a sequence of moves for the execution of Bishop and Knight checkmate on a magic square of the 8x8 board, a magic square of Al-Zarquali (11th century). The analysis delves into the evolution of the musical material used, showing the tendency to give rise to symmetries of pitches and temporal fragments between the different movements of the composition. These symmetries give rise to analogies with the concept of chirality, characteristic of the geometry of chess. Structures that show chirality appear in the work both in sound and temporal space.